Competence of Sunday School Teachers in Carrying Out The Great Commission of Matthew 28:19-20 Through Education in Sunday School - Ivo Christiana Siregar (Green Publisher Indonesia, 2023)
The competence of Sunday school teachers plays an important role in achieving the goal of Christian education in Sunday School, namely carrying out the great commission. This study aims to explain the competence of Sunday school teachers, education in Sunday schools and the great mandate in education. This research uses a library method with descriptive qualitative proximity, where researchers try to answer research problems by looking for literature sources related to research problems. The conclusion of this study is that there is a need for competent teachers so that the goal of Christian religious education in Sunday School can be realized. The way is that the church develops paedagogic competence, personality competence, social competence and professional competence of Sunday school teachers through a continuous set of spiritual development, knowledge and abilities